1999
DOI: 10.1111/j.1744-7348.1999.tb05261.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sheath tube length on leaf development in perennial ryegrass (Lolium perenne L.)

Abstract: Position in and contribution of leaf laminae to the canopy of forage grasses are important both in determining herbage growth rates and intake rate by grazing animals. These canopy characteristics are controlled by the way dry matter is apportioned between sheath and lamina in growing leaves. The objective of this work was to determine how the development of individual leaves is affected by altering the effective length of the psuedostem tube, on the assumption that the light environment within the tube varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 15 publications
3
30
0
Order By: Relevance
“…The physiological determinants are more obscure for LED than for LER. Several earlier studies have indicated that the sheath length of a mature leaf affects the final length of the following subtended leaf, and reduction in sheath tube length due to defoliation was the cause of the reduction in leaf length [47,64,102,103]. These studies suggest that the decrease in leaf length was associated with a decrease in LED.…”
Section: Consequences Of Defoliation On Leaf Lengthmentioning
confidence: 97%
“…The physiological determinants are more obscure for LED than for LER. Several earlier studies have indicated that the sheath length of a mature leaf affects the final length of the following subtended leaf, and reduction in sheath tube length due to defoliation was the cause of the reduction in leaf length [47,64,102,103]. These studies suggest that the decrease in leaf length was associated with a decrease in LED.…”
Section: Consequences Of Defoliation On Leaf Lengthmentioning
confidence: 97%
“…It appears that these cellular processes are under the influence of the length of the enclosing sheaths both directly and indirectly. Experimental modifications to incise or artificially increase the pseudostem tube length directly affected the length of the leaf elongation zone and the final length of the cells [63,64]. Furthermore, modification of the pseudostem tube length with, for example, an opaque plastic tube, could also indirectly affect cell dynamics via control of the timing of leaf tip emergence [65].…”
Section: Environmental and Genetic × Environmental Interaction Effectmentioning
confidence: 99%
“…Furthermore, modification of the pseudostem tube length with, for example, an opaque plastic tube, could also indirectly affect cell dynamics via control of the timing of leaf tip emergence [65]. Delaying or anticipating this event could modify both the placement of the sheath-blade boundary and the total cell number, as cessation of cell division at the base of the leaf could be triggered at the moment of leaf tip emergence from the previous sheath [63,64]. These effects may be light mediated.…”
Section: Environmental and Genetic × Environmental Interaction Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 60 kg N ha -1 extended epidermal cell size but number of photosynthetic cells were reduced in comparison to control leaf. Longer leaves and carbon partitioning in cell wall contents has been reported in grasses (Casey et al, 1999). The leaf size and weight relationship may discard the incorporation of nitrogen into protein thereby diverting into the structural components of leaf, cell walls and new cell formation in the lower epidermis to provide the support at the horizontal axis of stem with increasing supply of nitrogen.…”
Section: Leaf Enlargementmentioning
confidence: 99%